37.7k views
4 votes
Please help prove these identities!

Please help prove these identities!-example-1

1 Answer

5 votes

Hi! It will be a pleasure to help you to prove these identities, so let's get started:

PART a)

We have the following expression:


tan(\theta)cot(\theta)-sin^(2)(\theta)=cos^2(\theta)

We know that:


cot(\theta)=(1)/(cot(\theta))

Therefore, by substituting in the original expression:


tan(\theta)\left((1)/(tan(\theta))\right)-sin^(2)(\theta)=cos^2(\theta) \\ \\ \\ Simplifying: \\ \\ 1-sin^2(\theta)=cos^2(\theta)

We know that the basic relationship between the sine and the cosine determined by the Pythagorean identity, so:


sin^2(\theta)+cos^2(\theta)=1

By subtracting
sin^2(\theta) from both sides, we get:


\boxed{cos^2(\theta)=1-sin^2(\theta)} \ Proved!

PART b)

We have the following expression:


(cos(\alpha))/(cos(\alpha)-sin(\alpha))=(1)/(1-tan(\alpha))

Here, let's multiply each side by
cos(\alpha)-sin(\alpha):


(cos(\alpha)-sin(\alpha))\left((cos(\alpha))/(cos(\alpha)-sin(\alpha))\right)=(cos(\alpha)-sin(\alpha))\left((1)/(1-tan(\alpha))\right) \\ \\ Then: \\ \\ cos(\alpha)=(cos(\alpha)-sin(\alpha))/(1-tan(\alpha))

We also know that:


tan(\alpha)=(sin(\alpha))/(cos(\alpha))

Then:


cos(\alpha)=(cos(\alpha)-sin(\alpha))/(1-(sin(\alpha))/(cos(\alpha))) \\ \\ \\ Simplifying: \\ \\ cos(\alpha)=(cos(\alpha)-sin(\alpha))/((cos(\alpha)-sin(\alpha))/(cos(\alpha))) \\ \\ Or: \\ \\ cos(\alpha)=((cos(\alpha)-sin(\alpha))/(1))/((cos(\alpha)-sin(\alpha))/(cos(\alpha))) \\ \\ Then: \\ \\ cos(\alpha)=cos(\alpha).(cos(\alpha)-sin(\alpha))/(cos(\alpha)-sin(\alpha)) \\ \\ \boxed{cos(\alpha)=cos(\alpha)} \ Proved!

PART c)

We have the following expression:


(cos(x+y))/(cosxsiny)=coty-tanx

From Angle Sum Property, we know that:


cos(x+y)=cos(x)cos(y)-sin(x)sin(y)

Substituting this in our original expression, we have:


(cos(x)cos(y)-sin(x)sin(y))/(cosxsiny)=coty-tanx

But we can also write this as follows:


\\ (cosxcosy)/(cosxsiny)-(sinxsiny)/(cosxsiny)=coty-tanx \\ \\ Simplifying: \\ \\ (cosy)/(siny)-(sinx)/(cosx) =coty-tanx \\ \\ But: \\ \\ (cosy)/(siny)=coty \\ \\ (sinx)/(cosx)=tanx \\ \\ Hence: \\ \\ \boxed{coty-tanx=coty-tanx} \ Proved!

PART d)

We have the following expression:


\ln\left|1+cos \theta\right|+\ln\left|1-cos \theta\right|=2\ln\left|sin \theta\right|

By Logarithm product rule, we know:


log_(b)(x.y) = log_(b)(x) + log_(b)(y)

So:


\ln\left|1+cos \theta\right|+\ln\left|1-cos \theta\right|=\ln\left|(1+cos \theta)(1-cos \theta)\right|

The Difference of Squares states that:


a^2-b^2=(a+b)(a-b) \\ \\ So: \\ \\ (1+cos \theta)(1-cos \theta)=1-cos^2 \theta

Then:


\ln\left|(1+cos \theta)(1-cos \theta)\right|=\ln\left|1-cos^(2) \theta\right|

By the Pythagorean identity:


sin^2(\theta)+cos^2(\theta)=1 \\ \\ So: \\ \\ sin^2 \theta = 1-cos^2 \theta

Then:


\ln\left|1-cos^(2) \theta\right|=\ln\left|sin^2 \theta|

By Logarithm power rule, we know:


log_(b)(x.y) = ylog_(b)(x)

Then:


\ln\left|sin^2 \theta|=2\ln\left|sin \theta|

In conclusion:


\boxedsin \theta\right \ Proved!

User Jeahel
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.